2022
DOI: 10.1007/s12281-022-00429-x
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis in Children: Case series and Narrative Review

Abstract: Purpose of Review Pediatric sporotrichosis has not been sufficiently studied; this review aims to evaluate the risk and prognostic factors related to the development of sporotrichosis associated to this age group. Also, we want to evaluate the causes of the increased number of cases of sporotrichosis in the pediatric population such as environmental changes in endemic areas, the biodiversity, and virulence among the pathogenic clade causing sporotrichosis in different areas of the globe, and espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 74 publications
(131 reference statements)
1
32
2
10
Order By: Relevance
“…27,32 Ageing could be the factor that affects assay sensitivity. 24,31,34 In this study, we observed a lower frequency of false negatives in children (12%) compared with adults (18%), but this was not statistically significant. To increase the chance of detecting cases, it is recommended to evaluate acute and convalescent specimens.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…27,32 Ageing could be the factor that affects assay sensitivity. 24,31,34 In this study, we observed a lower frequency of false negatives in children (12%) compared with adults (18%), but this was not statistically significant. To increase the chance of detecting cases, it is recommended to evaluate acute and convalescent specimens.…”
Section: Discussioncontrasting
confidence: 58%
“…CTS was defined following the guidelines of the Brazilian ministry of health (Appendix A). 24,25 Mycological studies were done with those patients where access to specimens was possible. All CTS cases were treated and followed during their time at the HC-UFPR.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations